The Use of “LIBAT” Methods (See – Read – Write) to Improve Student Learning Outcomes in Arabic Lenguage Subjects Kitabah Materials - Ade Arip Ardiansyah; Alna Ningsih; Iis Barokah (UIN Sunan Gunung Djati Bandung, 2023)
This research stems from the problems of teaching Arabic that students feel in the ninth grade at